Interpreting the contemporary Chinese planning from the “new towns” perspective: The case studies of Pujiang and Kilamba - Bona, Domenica (International Planning History Society Proceedings, 2018)
The new millennium has been a time for a great change in the Chinese planning history. Planning has become a professional practice able to manage the construction of thousands of new urban settlements and urbanization has driven deep transformations in the economic structure of China and in its society. This paper proposes a critical interpretation of the “new towns” by analysing two case studies, Pujiang and Kilamba. Pujiang is a new town near Shanghai designed by the Italian firm Gregotti Associati with the local Highpower-OCT Investment; Kilamba was designed by the Chinese CITIC in the outskirt of Luanda, Angola. From a planning perspective, this paper tries to analyse the phenomenal and formal aspects related to plans of two case studies. Applying a typo-morphological approach, the physical structure of both plans are analysed and compared so to highlight the structural elements of analogy between them. The aim is to reveal the current attempts by planners to transfer cultural issues into the built environment. Thus, this will allow to find out the possible commonalities and define the terms of correspondences of these contemporary layouts with the historical Chinese planning wisdom.